Media Gambar Sebagai Alat Bantu dalam Pembelajaran Rantai Makanan pada Siswa Kelas IV MI Syirkah Salafiyah Jember - Stella Dinda Dian Adisti; Suwignyo Prayoga; Wardah Agustina; Marcella Dwi (Universitas Palangka Raya, 2025)
The use of picture media has proven to be effective in supporting the learning process. This study aims to enhance students’ understanding of the food chain concept through the use of visual media in science learning for fourth-grade students at MI Syirkah Salafiyah. Initial observations indicated that many students had difficulty grasping the concept due to its abstract nature and the limited use of visual aids during instruction. To address this issue, the study employed Classroom Action Research (CAR), conducted over two cycles. The research involved 25 fourth-grade students as participants. Data were collected through observation, learning outcome tests, and documentation. The findings showed that the application of picture media significantly improved students’ comprehension, as evidenced by the increase in average test scores across the cycles. Moreover, students appeared more engaged, enthusiastic, and better able to understand the food chain concept when supported by relevant visuals. Therefore, the use of image-based media adapted to the characteristics of elementary students is strongly recommended, especially for teaching complex science topics.